2020
DOI: 10.3390/cells9071583
|View full text |Cite
|
Sign up to set email alerts
|

Vasculopathy and Coagulopathy Associated with SARS-CoV-2 Infection

Abstract: The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of coronavirus disease 2019 (COVID-19), has resulted in >500,000 deaths worldwide, including >125,000 deaths in the U.S. since its emergence in late December 2019 and June 2020. Neither curative anti-viral drugs nor a protective vaccine is currently available for the treatment and prevention of COVID-19. Recently, new clinical syndromes associated with coagulopathy and vasculopathy have emerged as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
84
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 230 publications
0
84
0
8
Order By: Relevance
“…6 One of the theories that appear to have been playing a role is the selectivity of coronavirus toward angiotensin-converting enzyme 2 (ACE2) receptors. 7 On binding to cell surface ACE2 receptors, it inhibits the vaso-protective functions of ACE, causing pro-inflammatory and prothrombotic states. In addition, the systemic increase of pro-inflammatory cytokines such as interleukin-6 is also believed to be a major contributor of inducing hypercoagulable state in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 One of the theories that appear to have been playing a role is the selectivity of coronavirus toward angiotensin-converting enzyme 2 (ACE2) receptors. 7 On binding to cell surface ACE2 receptors, it inhibits the vaso-protective functions of ACE, causing pro-inflammatory and prothrombotic states. In addition, the systemic increase of pro-inflammatory cytokines such as interleukin-6 is also believed to be a major contributor of inducing hypercoagulable state in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the systemic increase of pro-inflammatory cytokines such as interleukin-6 is also believed to be a major contributor of inducing hypercoagulable state in COVID-19. Furthermore, COVID-19 compromises the integrity of endothelial monolayer by causing endothelial cell death through its lytic replication, 7 thus exposing the thrombogenic basement membrane and in turn leading to the activation of coagulation cascade. 7 Acknowledging that SARS-CoV-2 leads to a hypercoagulable state, the role of anticoagulation is important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cardiovascular complications of COVID-19 have drawn more attention from both clinicians and investigators, although the exact mechanism for the myocardial injuries caused by SARS-CoV-2 is not completely understood [ 89 – 91 ]. Recently, new clinical syndromes associated with coagulopathy and vasculopathy have emerged as a cause of sudden death and other serious clinical manifestations in younger COVID-19 patients [ 90 ]. Angiotensin-converting enzyme 2 (ACE2), the receptor for SARS-CoV-2 and other coronaviruses, is a transmembrane protein expressed by lung alveolar epithelial cells, enterocytes, and vascular endothelial cells whose physiological role is to induce the maturation of angiotensin I to generate angiotensin 1-7, a peptide hormone that controls vasoconstriction and blood pressure [ 92 , 93 ].…”
Section: Sars-cov-2-induced Cardiovascular Injuriesmentioning
confidence: 99%
“…in a study of diabetic and obese patients with COVID-19, have suggested that serum amyloid may play a key role in the pathogenesis of COVID-19, in addition to potentially having a prognostic role. COVID-19 includes an evolving set of clinical manifestations, including stroke and cardiomyopathies associatedwith coagulopathy and vasculopathy, which can cause sudden death and other serious morbidities[71]. A study by Fogarty, et al[72] has shown that race and ethnicity have major effects upon thrombotic risk, with significantly lower risk in Chinese compared to Caucasian individuals.…”
mentioning
confidence: 99%